PENGARUH PELAKSANAAN KANTIN KEJUJURAN DALAM MEMBENTUK AKHLAK SISWA DI SDN 114 PALEMBANG - Nyimas Atika (El-Idare, 2016)
This study investigates the honesty canteen program management of the SDN 114 Palembang and how much influence the honesty canteen program management in shaping the character of students at SDN 114 Palembang. Honesty is one of the main attitudes that have a significant contribution to the anti-corruption behavior. This study uses quantitative data analysis using product moment correlation product to determine how much influence the honesty canteen program in shaping the character of students by the total of respondents 40 people. For each student answer score is calculated using the percentage of the frequency distribution table, then use a formula product moment. Based on these findings we can conclude that, the management here is to organize, manage, define, implement and oversee the move or has been good but not optimal. While the influence of the honesty of the school canteen in shaping the character of students at SDN 114 Palembang showed steeper levels.